Perancangan al-Quran Player untuk Tunanetra menggunakan Mikrokontroler dan DFPlayer - Hidayat Hidayat; Linda Nurjanah (Komputika : Jurnal Sistem Komputer, 2018)
ABSTRACT – The limited number of electronic devices for blind people that can assist them in learning and memorizing the Koran encourages researchers to design electronic devices for the al-Quran Player for blind people. The electronic device is designed by utilizing the ATMega128 microcontroller as the main controller unit and the DFPlayer module as a decoder to convert digital files into audio. All suras and verses of the al-Quran in mp3 format are stored on the memory card that will be read by the DFPlayer module. This al-Quran player is expected to make it easier for blind people to learn the pronunciation of the al-Quran properly and correctly. Keywords – al-Quran Player; Blind people; DFPlayer mini; Microncontroller ATMega128